Factors Predicting Occurrence of Intimate Partner Violence During Pregnancy Among Thai Pregnant Woman - Nareerat Boonnate (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Intimate partner violence (IPV) during pregnancy occurs throughout the world. This issue is a large concern for community and society because it not only carries health risks for the woman but also affects child health. This cross-sectional study aimed to examine factors predicting the occurrence of IPV during pregnancy. Two hundred and thirty pregnant women, attending the prenatal clinic at a university hospital were purposively selected to participate. Six questionnaires were used to collect data: demographic data form, the revised Rosenberg Self-Esteem Scale, the A-Z Stress Scale, the revised Multidimensional Scale of Perceived Social Support, the Kansas Marital Satisfaction Scale, and the Index of Spousal Abuse. The reliability coefficients of all instruments were found to be acceptable, ranging from .80 to .96. Descriptive statistics and binary logistic regression were employed to analyze the data. Results revealed that the prevalence of IPV during pregnancy was 11.7%, with physical, non-physical and both physical and non-physical abuse occurring at rates of 3.5%, 4.3%, and 3.9% respectively. Binary logistic regression demonstrated that stress (OR = 1.03; 95% CI, 1.01-1.04) and marital satisfaction (OR = .84; 95% CI, .73 - .96) were significant predictors of IPV during pregnancy. These two co-predictors could explain 26.3% (by Negelkerke R2) of the total variance for occurrence of IPV during pregnancy. The findings of the study provide health care providers with a better understanding of the risk factors for the occurrence of intimate partner violence during pregnancy. It is recommended that screening for IPV should be done on a routine basis as part of nursing care during the first prenatal visit. Furthermore, counseling should be provided for pregnant women affected by IPV to prevent severe consequences on mother and unborn child.